2016
DOI: 10.1038/boneres.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility with osteogenic cells and enhanced in vivo anti-infection potential of quaternized chitosan-loaded titania nanotubes

Abstract: Infection is one of the major causes of failure of orthopedic implants. Our previous study demonstrated that nanotube modification of the implant surface, together with nanotubes loaded with quaternized chitosan (hydroxypropyltrimethyl ammonium chloride chitosan, HACC), could effectively inhibit bacterial adherence and biofilm formation in vitro. Therefore, the aim of this study was to further investigate the in vitro cytocompatibility with osteogenic cells and the in vivo anti-infection activity of titanium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…As a biodegradable nontoxic biopolymer derived from chitosan, quaternized chitosan exhibits satisfactory antimicrobial activity and biocompatibility both in vitro and in vivo, as elaborately described in our previous studies. 15 17 Moreover, we also found that quaternized chitosan-coated sutures showed comparable anti-infection potential and cytocompatibility with triclosan-coated sutures. 18 It has been verified that quaternized chitosan with positively charged quaternary ammonium groups exerts broad-spectrum antimicrobial effects via electrostatic interactions with microbes with negatively charged phosphoryl groups, thus affecting the cytoplasmic membrane integrity.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…As a biodegradable nontoxic biopolymer derived from chitosan, quaternized chitosan exhibits satisfactory antimicrobial activity and biocompatibility both in vitro and in vivo, as elaborately described in our previous studies. 15 17 Moreover, we also found that quaternized chitosan-coated sutures showed comparable anti-infection potential and cytocompatibility with triclosan-coated sutures. 18 It has been verified that quaternized chitosan with positively charged quaternary ammonium groups exerts broad-spectrum antimicrobial effects via electrostatic interactions with microbes with negatively charged phosphoryl groups, thus affecting the cytoplasmic membrane integrity.…”
Section: Introductionsupporting
confidence: 52%
“…Quaternized chitosan was prepared by combining glycidyl trimethylammonium chloride and chitosan as previously reported. 15 18 A 10 mM vemurafenib solution was produced by dissolving the chemical in 1 mL DMSO (Sigma-Aldrich Co.).…”
Section: Methodsmentioning
confidence: 99%
“…By determining the work of adhesion, the interaction of cells with the metallic implant surfaces can be predicted. In the literature, it was reported that a higher value of work adhesion than 60 mN/m indicated a high adhesion of the cell to implant surface [59]. Moreover, it was demonstrated that the osteonectine and osteocalcin genes were more attached to the hydrophilic surfaces with high work adhesion [59,60].…”
Section: Alloysmentioning
confidence: 99%
“…The cell viability of the various sample surfaces was analyzed by a Live/Dead Cell kit (ab115347, Abcam, United Kingdom) as described previously ( Yang et al, 2016a ). After co-culturing for 24 h, the samples were stained with 500 μL of a combination dye for 10 min, and then detected by CLSM.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial viability on various sample surfaces was analyzed using a Live/Dead BacLight viability kit (Thermo Fisher Scientific, United States) ( Yang et al, 2016a ). Briefly, after co-culturing for 24 h, the samples were stained with 500 μL of a combination dye and visualized by CLSM.…”
Section: Methodsmentioning
confidence: 99%